PENGARUH LAMA FERMENTASI DENGAN MEDIA TRAMETES SP. TERHADAP ORGANOLEPTIK, KADAR AIR DAN LEMAK PADA LIMBAH DAUN NENAS DI LAMPUNG TENGAH - Rahmadi Saputro; Farida Fathul; Yusuf Widodo (JURNAL ILMIAH PETERNAKAN TERPADU, 2015)
The main problem in the development of ruminant production in Indonesia was difficult to meet both continuous a vailability of feed quality and quantity. The abundance of pineapple leaves in Central Lampung province causing potentially a pineapple leaf feed stuffs. But the pineapple leaves have a high crude fiber content. Therefore, it will be fermented with pineapple leaves the treatment to reduce the high crude fiber content. This study aims to determine the effect of fermentation time best and know the effect of Trametes sp. The moisture content, fat content, and protein content of pineapple leaves.This study was done in the Laboratory of Animal Feed, Department of Animal Husbandry, Faculty of Agriculture, University of Lampung. The treatments were arranged by using Completely Randomized Design (CRD) with four treatments and four replications. The treatment consisted of storage during 0 day, 2 days, 4 days, 6 days. The dates of observation was analyzed by using variance analysis with significant level of 5% and or 1%. The polynomial orthogonal was used after the variance analysis showed the significant result.The results showed that treatment with fermentation time 0 days, 2 days, 4 days, and 6 days was highly significant (P <1%) of the moisture content, protein content, organoleptic and a significant (P <5%) of the fat content. Long fermentation close relationship with water, protein and fat. According to the regresion equality of water content Y=87,89-0,61x (R2=0,84, r=0,91), fat contentY=3,22+0,80x (R2=0,37, r=0,7), and protein contentY=14,51-1,52x (R2=0,82, r=0,91).